The Power of Social Media in Creating Branding Awareness for Hospital Customers at Teaching Hospital of Dental and Oral in Semarang - Eka Yunila Fatmasari; Wulan Kusumastuti (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2025)
Social media as a marketing communication tool can be a strategy for creating customer branding awareness. Strong branding awareness can attract potential new customers and turn existing customers into loyal ones. The decline in patient visits at the hospital is one of the things that needs to be addressed through one of the marketing efforts with social media. The aim of this research is to analyze the power of social media in creating customer branding awareness at X Teaching Hospital of Dental and Oral in Semarang. This research is a descriptive study with a cross-sectional approach. The sample in this study consisted of 100 outpatients. Data collection utilized a questionnaire that has been tested for validity and reliability. Secondary data regarding the use of Instagram social media is examined based on reach rate, engagement, follower growth, and profile visits. Data were analysed with quantitative descriptive statistics using frequency distribution measurements. Good branding awareness was demonstrated by 54% of respondents, while poor branding awareness was indicated by 46% of respondents. Based on secondary data studies, it is known that there has been a decline in hospital Instagram visits in terms of reach rate, engagement, follower growth, and profile visits. It was concluded that social media has significant power in creating customer branding awareness and impacts decisions to utilize health services.